Jean-Paul Sartre - Scriven, Michael. author. aut Link
XV, 193 p.
Keywords: This book offers an assessment of Sartre as an exemplary figure in the evolving political and cultural landscape of post-1945 France. Sartre's originality is located in the tense relationship that he maintained between deeply held revolutionary political beliefs and a residual yet critical attachment to traditional forms of cultural expression. A series of case-studies centred on Gaullism, communism, Maoism (Part 1), the theatre, art criticism and the media (Part 2), illustrate the continuing relevance and appeal of Sartre to the contemporary world.